Gwarancja: [Guarantee] (Studia Prawnicze / The Legal Studies, 1960)
Autor artykułu przedstawia swoje rozważania nad instytucją gwarancji, w kontekście umów kupna-sprzedaży oraz o dzieło. Przemyślenia są także osadzone w szerszym kontekście, ponieważ autor zajmuje się instytucją gwarancji nie tylko z punktu widzenia stosunków pomiędzy organizacjami socjalistycznymi bądź stosunków organizacji socjalistycznych – obywatel, lecz ponadto w świetle pojęć używanych w orzecznictwie i literaturze niektórych krajów bloku zachodniego. Autor przedstawia etymologię oraz definicję terminu gwarancja. Przybliża funkcjonowanie klauzul gwarancyjnych, tj. opisuje ich rodzaje, stosunek klauzuli gwarancyjnej do przepisów o rękojmi ustawowej. Koncentruje swoją uwagę także na gwarancjach terminowych oraz fabrycznych. Ponadto przedstawia funkcjonowanie instytucji gwarancji w gospodarkach socjalistycznych, porównując obowiązujące przepisy w Polskiej Rzeczypospolitej Ludowej, Niemieckiej Republice Demokratycznej i Czechosłowacji. The author of this article presents his reflections on the institution of warranty, in the context of sale and purchase contracts and works contracts. The reflections are also set in a broader context, as the author deals with the warranty not only from the point of view of relations between socialist organisations or relations between socialist organisations and the citizen, but, moreover, in the light of concepts used in the jurisprudence and literature of some Western Bloc countries. The author presents the etymology and definition of the term warranty. He introduces the operation of warranty clauses, i.e. describes their types, the relationship of the warranty clause to the statutory warranty provisions. He also focuses on date-based and factory warranty. In addition, the functioning of the warranty in socialist economies is described, comparing the applicable legislation in the People's Republic of Poland, the German Democratic Republic and Czechoslovakia.